Legal Politics of Interreligious Relations within the Pluralism Framework in Indonesia - I Putu Sastra Wibawa (International Journal of Interreligious and Intercultural Studies, 2020)
Religious diversity contributes to nation building positively. However, it can also be a potential source of conflict. The multi-religious communities in Indonesia face many conflicts that triggered by religion. This problem demands a strategic anticipation, especially in juridical view. Juridical anticipation means the state frames legal policies that regulate the relations between religious communities in Indonesia in order to achieve a harmonious life. The political law of interreligious harmony established by the government in Indonesia will unable to implement properly if indirectly intervene by the community. The public must keep discussing and seeking to maintain inclusive relations between religious communities to achieve religious harmony in Indonesia which is based on tolerance and cooperation in the life of society, nation and state.